2008
DOI: 10.1016/j.addr.2007.10.016
|View full text |Cite
|
Sign up to set email alerts
|

The design of guanidinium-rich transporters and their internalization mechanisms

Abstract: The ability of a drug or probe to cross a biological barrier has historically been viewed to be a function of its intrinsic physical properties. This view has largely restricted drug design and selection to agents within a narrow log P range. Molecular transporters offer a strategy to circumvent these restrictions. In the case of guanidinium-rich transporters (GRTs), a typically highly water-soluble conjugate is found to readily pass through the non-polar membrane of a cell and for some across tissue barriers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
341
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 379 publications
(349 citation statements)
references
References 115 publications
(183 reference statements)
5
341
2
1
Order By: Relevance
“…Previously, the targeting of peptide-based imaging agents has been limited to extracellular or cell-surface targets because of the barrier function of the cellular membrane. However, efficient delivery of imaging probes to the cell interior using cell-penetrating peptides has greatly expanded potential applications for molecular imaging (26)(27)(28)(29)(30)(31), similar to advances with cell-penetrating peptides in therapy (32)(33)(34)(35). Delivery of optically quenched, activatable, peptide-based imaging probes to the intracellular compartment makes selective retention and signal amplification possible, improving sensitivity and signal-to-noise ratios, as well as increasing the number of biochemical processes that can be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the targeting of peptide-based imaging agents has been limited to extracellular or cell-surface targets because of the barrier function of the cellular membrane. However, efficient delivery of imaging probes to the cell interior using cell-penetrating peptides has greatly expanded potential applications for molecular imaging (26)(27)(28)(29)(30)(31), similar to advances with cell-penetrating peptides in therapy (32)(33)(34)(35). Delivery of optically quenched, activatable, peptide-based imaging probes to the intracellular compartment makes selective retention and signal amplification possible, improving sensitivity and signal-to-noise ratios, as well as increasing the number of biochemical processes that can be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of metabolic or endocytosis inhibitors also seemed to have no effect on cellular internalization. These experiments, along with the finding that inverse and retro forms of the peptide are as effective, led to the belief that cellular uptake involved an energyindependent, non-endocytotic process that was receptor independent [4,9,10,20].…”
Section: Direct Translocation Endocytosis: An Either/or Discourse?mentioning
confidence: 99%
“…Since the cellular uptake of arginine-rich peptides is dependent on a variety of factors, including temperature, incubation time, cell type, cargo type and size, linkage type and size [4,61], comparison between different experiments have been difficult, and has compounded the controversy surrounding the uptake mechanism. It has no doubt been recognized that more than one mechanism may be involved in TAT translocation activity.…”
Section: Direct Translocation Endocytosis: An Either/or Discourse?mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies by us and others have shown that GR-MoTrs enable or enhance the delivery of a variety of cargos-including small molecules, metals, imaging agents, iron particles, and proteins-into a variety of mammalian cell types (13)(14)(15)(16). GR-MoTr-drug conjugates have also advanced to clinical trials for various indications including stroke, psoriasis, and ischemic damage (17).…”
mentioning
confidence: 99%